Influence of Leadership Style and Work Environment on OCB: Case Study of Perum Perhutani Central Java Regional Division - Cesaria Laily Benita; Aris Puji Purwatiningsih; Kusni Ingsih; Febrianur Ibnu (International Journal of Economics, Management and Accounting, 2025)
This study aims to identify the influence of leadership style and work environment on organizational citizenship behavior of employees of Perum Perhutani, Central Java regional division in Semarang city. This study uses quantitative methods. Data collection using questionnaire instruments that are distributed directly, and analysis using IBM SPSS Statistics. The results show that leadership style has a positive effect on OCB, while the work environment does not affect OCB. Therefore, Perum Perhutani is expected to improve its work environment so that loyalty and organizational citizenship behavior increase. Further researchers are expected to explore other related objects and variables, such as in the banking sector, and employee satisfaction in further research.